LIMB GIRDLE SYNDROMES: MYASTHENIA OR MYOPATHY. Issue 12 (15th November 2016) - Cruz, Pedro Rodriguez; Belaya, Katsiaryna; Cossins, Judy; Liu, Wei Wei; Maxwell, Susan; Petty, Richard; Farrugia, Maria; Walls, Timothy; Beeson, David; Palace, Jacqueline
Abstract : Congenital myasthenic syndromes (CMS) are disorders caused by mutations in genes encoding proteins that are essential for maintaining the integrity of neuromuscular transmission. In recent years we have identified an unexpected relationship between glycosylation defects and CMS by using next generation sequencing. Patients with mutations affecting the early stages of glycosylation constitute a clinically distinctive group of disorders. Unlike other CMS subtypes, the presentation is delayed beyond infancy with prominent limb-girdle weakness and minimal or absent craniobulbar manifestations. In fact, we find that they occur in the absence of classic myasthenic manifestations such as ptosis, ophthalmoplegia or facial weakness, and therefore are likely to be under-diagnosed. In addition, the presence of additional features such as mild cognitive delay, cataracts, raised CK levels, myopathic abnormalities on muscle biopsy and muscle MRI, and selective abnormalities of neuromuscular transmission on electrophysiological testing, make them easily misdiagnosed as myopathies or muscular dystrophies. The recognition of these disorders is important since they can be treated symptomatically with cholinesterase inhibitors.